Adenine phosphoribosyl transferase deficiency leads to renal allograft dysfunction in kidney transplant recipients: a systematic review - Rashid,Ishfaq (2022)
Abstract Background: Adenine phosphoribosyl transferase (APRT) deficiency has great implications on graft survival in kidney transplant patients. This systematic review investigated the diagnostic pattern, treatment approach, and kidney transplant outcomes among kidney transplant patients with adenine phosphoribosyl transferase deficiency. Material and methods: Articles reporting the APRT enzyme deficiency and kidney allograft dysfunction were retrieved from PubMed/Medline, ScienceDirect, Cochrane library and Google scholar databases. Descriptive analysis was used to draw inferences. Results: The results from 20 selected studies covering 30 patients receiving 39 grafts had an average age of 46.37 years are presented. Graft survival time of more than 6 months was reported in 23 (76.7%) patients, while other 7 (23.3%) patients had graft survival time of less than 6 months. Only 4 (13.3%) patients had APRT deficiency before transplantation. After follow-up, one-third of the patients 10 (33.3%) had stable graft function, 1 patient had allograft loss, 8 (26.6%) patients had delayed graft function while the remaining 11 (36.6%) patients had chronic kidney graft dysfunction. Conclusions: APRT deficiency is an under-recognized, treatable condition that causes reversible crystalline nephropathy, leading to loss of allograft or allograft dysfunction. The study results showed that inclusion of genetic determination of APRT deficiency in the differential diagnosis of crystalline nephropathy, even in the absence of a history of nephrolithiasis, can improve renal outcomes and may improve allograft survival.